Karakteristik dan Faktor Pendorong Minat Petani Muda Pada Komoditas Hortikultura di Kecamatan Alor Timur Laut Kabupaten Alor - Gerson Hans Maure (Jurnal Ilmiah Wahana Pendidikan, 2023)
Sustainable agricultural development is highly dependent on the role of human resources. The results of the 2013 agricultural census showed that the share of agricultural households for the group of young farmers aged <35 years was only 12.87%, much lower than middle age (35-54 years) 54.37% and elderly farmers (over 54 years) 32.76%. . For this reason, it is necessary to conduct research to determine the characteristics and factors driving young farmers' interest in farming and the research location is focused on Northeast Alor District, Alor Regency. The research was carried out for 4 months, namely April - July 2022 in Northeast Alor District in Kamot village, Air Mancur village and Nailang village in 60 respondents using a questionnaire. The results showed that the average age of young farmers in Northeast Alor sub-district was 30.2 years, interest in farming emerged from university graduates, youth awareness to use their own land for agriculture, even with limited land and costs. In addition, the interest of youth in Northeast Alor sub-district to do horticulture farming is in the moderate category. Thus it is necessary to increase youth interest (Y) in horticultural farming by increasing external factors (X2) and motivation (X3). Keywords ; sustainable agriculture, interests, young farmers, horticulture